Stability of Nuclear and Mitochondrial Reference Genes in Selected Tissues of the Ambrosia Beetle Xylosandrus germanus - Nisha Patwa; Christopher M. Ranger; Maximilian Lehenberger; Peter H. Biedermann; Michael E. Reding (Insects, 2021)
The fungus-farming ambrosia beetle Xylosandrus germanus (Blandford) uses a pouch-like structure (i.e., mycangium) to transport spores of its nutritional fungal mutualist. Our current study sought to identify reference genes necessary for future transcriptome analyses aimed at characterizing gene expression within the mycangium. Complementary DNA was synthesized using selected tissue types from laboratory-reared and field-collected X. germanus consisting of the whole body, head + thorax, deflated or inflated mycangium + scutellum, inflated mycangium, and thorax + abdomen. Quantitative reverse-transcription PCR reactions were performed using primers for 28S ribosomal RNA (28S rRNA), arginine kinase (AK), carbamoyl-phosphate synthetase 2-aspartate transcarbamylase-dihydroorotase (CAD), mitochondrial cytochrome oxidase 1 (CO1), and elongation factor-1α (EF1α). Reference gene stability was analyzed using GeNorm, NormFinder, BestKeeper, ΔCt, and a comprehensive final ranking by RefFinder. The gene CO1 was identified as the primary reference gene since it was generally ranked in first or second position among the tissue types containing the mycangium. Reference gene AK was identified as a secondary reference gene. In contrast, EF1α was generally ranked in the last or penultimate place. Identification of two stable reference genes will aid in normalizing the expression of target genes for subsequent gene expression studies of X. germanus’ mycangium.